PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP KETERAMPILAN SAINS DAN HASIL BELAJAR SISWA KELAS VIII TENTANG IPA SMP ADVENT PALU - Susanti, Eva (JSTT, 2016)
This research is based on learning paradigm centered on students. Unmotivated learning model has not been applied to the students that leading them active in searching and finding concept. It is the reason for conducting the research. The research aims to describe the effect of learning model of discovery learning towards science skill about natural science of SMP Advent Palu and describe the effect of the learning model towards students learning outcomes of the eight grade of SMP Advent Palu. This research employed quasi experimental method with Non-equivalent Pretest-Posttest group Design. The population was 40 students divided into two classes. The data collected was posttest score which analyzed using t test. The research reveals that there is an effect of discovery learning model towards students’ science skill and students learning outcomes.